BSEd-English Students’ Acceptance of ChatGPT in Language Education Research course: A Literature Review - Christian Loid Valenzuela; Wilma Balon (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
Generative artificial intelligence, such as ChatGPT, is increasingly used in higher education, yet its implications for research pedagogy in the Philippine context remain underexplored. This literature review synthesizes empirical and theoretical studies on ChatGPT’s application in academic writing, student engagement, ethical considerations, and higher-order research tasks, including qualitative data analysis. The evidence indicates that ChatGPT enhances idea generation, drafting, revision, engagement, and metacognitive skills, with benefits amplified when embedded in structured pedagogical design. However, research predominantly addresses general writing tasks, offering limited insight into how students critically engage with AI outputs, navigate ethical challenges, or operationalize higher-order research processes. Institutional policies, digital literacy, and unequal access further shape student experiences, and longitudinal impacts on research competence, critical thinking, and ethical behavior remain largely unexamined. These findings highlight the necessity of context-sensitive pedagogical frameworks that support responsible AI use, maintain academic integrity, and foster sustainable research competence. Treating ChatGPT as a research-pedagogical priority rather than a mere technical tool enables Philippine higher education institutions to leverage AI as a catalyst for transformative learning and capability development, mitigating the risk of superficial or inequitable implementation.